DETERMINAN KOMITMEN ORGANISASI DOSEN DI WILAYAH KOPERTIS IV - Mr Wahyudi (Universitas Pamulang, 2018)
This study aimed to analyze and prove the influence of compensation, work discipline and work environment on motivation, and its implication toward lecturer's commitment, both partially and simultaneously. The method used in this research were descriptive, survey and explanatory method with population size of 1.339 and sample size of 224 respondents. The method used to analysis data was SEM (Structural Equation Modeling). The research result, obtained the findings as follows: The compensation and work environment both partially had positive and significant impact on work motivation, but work discipline hadn’t significant effect. However, as simultaneously exogenous variables had positive and significant impact on work motivation with contribution (R2) 50%. Partially compensation dominantly influence on work motivation. Further on Structural 2 showed those:, The compensation, work discipline, work environment and work motivation both partially and simultaneously had positive and significant impact on lecturer's commitment with contribution (R2) 76%. Viewed as partial, compensation had dominantly toward lecturer's commitment. Concerning on direct and indirect effect that work motivation was being partial mediating. This study found and recommended that to increase lecturer's commitment needed to be extending work motivation, reflected by the dimension of affiliation which supported with an increase in compensation which reflected by the dimensions of none financial, especially appreciation, and repaired on work discipline particularly prevent dimension as well as corrected on work environment specially relationships. Key Words: Compensation, Work Discipline, Work Environment, Work Motivation, Lecturer's Commitment.